KESESUAIAN GAYA VISUALISASI ANTROPOMORFISME DALAM DESAIN BIOPHILIC UNTUK MEDIA ANAK USIA PRASEKOLAH - Anastasia Dinda Ciptaviana; Nedina Sari; Dianing Ratri (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2023)
This research is motivated by preschoolers' need for appropriate visualizations of living things in media. Although naturally, human's sense of biophilia encourages children's interest and interactions with nature, these interactions, conducted routinely and of quality, are now a privilege that only a few have. In this condition, media with anthropomorphic visualizations of living things is often used as a complementary method of honing children's real intelligence from a young age. However, view's regarding its effectiveness is still debated. Because of this, through an integrative literature review regarding the psychological development of preschoolers, anthropomorphic visualizations, and the human's sense of biophilia, the researcher attempts to analyze the potential of anthropomorphic visualizations in preschoolers' media for nature education from each field's point of view. Design practitioners and subsequent researchers may benefit from this research as a basis for appropriate anthropomorphic visualizations in children's media applications. The literature review process utilizes features from several online scientific article research portals or services. This process begins with determining selection based on keywords, titles and abstracts, complete articles, and gradual analysis based on input from each field, as well as the integrative analysis between fields. Results show that the effectiveness of nature education with anthropomorphic visualizations on the development of naturalist intelligence in preschool-age children cannot be generalized. The impact of visualization styles is adjustable depending on design goals, such as emotional attachment or scientific knowledge. Keywords: anthropomorphism, biophilia, children's media, preschool, visualization